Uji Aktivitas Antimikroba dari Ekstrak Metanol Teripang Asal Perairan Lampung - Untari, Febriana; Rasyid, Abdullah; Murniasih, Tutik; Wibowo, Joko Tri (LPPM Universitas Terbuka, 2025)
Sea cucumbers possess various biological activities, including antihypertensive, antioxidant, anticoagulant, antimicrobial, hemolytic, cytotoxic, and immunomodulatory properties. These activities are attributed to the presence of primary and secondary metabolites in sea cucumbers, such as peptides, vitamins, minerals, fatty acids, saponins, steroids, carotenoids, collagen, gelatin, chondroitin sulfate, and amino acids. This study aims to evaluate the antimicrobial activity of methanol extracts from several sea cucumber species collected from Lampung waters. The agar disk diffusion method was used in the study. The results of methanol extracts from five sea cucumber species tested againts five microbial species showed varying outcomes. The highest yield of sea cucumber methanol extract was found in Bohadschia marmorata (3.88%), while the lowest was Metriatyla lessoni (2.68%). In the antibacterial potential test, no antibacterial activity was observed against the four tested bacteria. However, the fungus Candida albicans exhibited an inhibition zone. Four sea cucumber species demonstrated antifungal potential against C. albicans, with the following inhibition zone diameters: B. Marmorata (13.35 ± 2.76 mm), Holothuria lessoni (12.9 ± 0.71 mm), Stichopus quadrifasciatus (10.4 ± 0 mm), and Holothuria leucospilota (8.25 ± 0.07 mm).